Tourism and development concepts and issues - Boyd, Stephen W.; Sharpley, Richard 1956-; Telfer, David J. (Bristol, UK Buffalo Channel View Publications, 2015)
This book explores and challenges the relationship between tourism and development and establishes a conceptual link between the discrete yet interconnected disciplines of tourism studies and development studies. This revised and expanded second edition provides not only a comprehensive theoretical foundation in development studies but also a critical analysis of contemporary themes and issues relevant to the study of tourism and its potential contribution to development. The second edition contains new chapters on the following topics: Tourism and Poverty Reduction-- Cultural Heritage, Tourism and Socio-economic Development--Tourism, Climate Change and Development--Human Rights Issues in Tourism Development-- Tourism, Development and International Studies
Includes bibliographical references and index.
Keywords: Tourism; Economic development